Characterizati on of sisal/polypropylene composites treated with plasma - Muralidhar, B. A. (Array, 2020)
In this study, sisal/polypropylene composites were experimentally investigated for their flexural, thermal and water absorption characteristics. The effect of oxygen (O), argon (Ar) and ammonia (NH3) plasmas on the surface of the sisal fibre as well as the effect of the sisal fibre content on the above mentioned properties was studied. The composite laminates (4 mm thick) were processed by hand lay-up technique by using a compression moulding machine, with the mould temperature of 165oC and the pressure of 6.89 x 102 kPa for 15 minutes. Specimen preparation and testing were carried out as per ASTM standards. Flexural data obtained showed that the plasma-treated sisal fibre-reinforced polypropylene offered superior flexural properties compared to untreated laminates, which indicated better adhesion between the sisal fibre and the untreated polypropylene matrix. Thermal investigations revealed that the sisal/polypropylene composite had its thermal stability in between that of the fibre and the matrix. Furthermore, the water absorption studies indicated that plasma treatment decreased the water uptake of the laminates, thereby leading to better fibre-matrix adhesion. Morphological studies were carried out by using SEM to complement the results.